Pushing the boundaries: Integration of multi-source digital elevation model data for seamless geological mapping of the UK's coastal zone. (11th September 2015) - Westhead, Keith; Smith, Kay; Campbell, Evelyn; Colenutt, Andrew; McVey, Stuart
ABSTRACT Recent advances in marine acoustic survey and land-based topographic monitoring technologies have resulted in increasingly cost-effective data acquisition in coastal areas. The DEFRA-funded National Network of Regional Coastal Monitoring Programmes of England are, for example, utilising swath bathymetry and airborne light detection and ranging (LiDAR) technology more routinely to survey the coastal zone around the coastline of England. The demand for data processing, visualisation and interpretation techniques to keep pace with such advances in data acquisition is clear. This study discusses collection and processing techniques for such data on the south coast of Dorset, England, which have enabled the production of a seamless, high spatial resolution digital elevation model across the coastal zone. Case studies demonstrate how this elevation model can be viewed and analysed using state-of-the-art digital techniques to allow geological mapping to be extended from onshore to offshore in unprecedented detail, effectively eliminating what is known as the 'White Ribbon' for coastal geological mapping. The potential for rolling out such techniques for wider surveying programmes across many environmental disciplines is significant, which could contribute towards improving the multi-disciplinary scientific evidence base in the complex coastal zone.